Три женщины в городском пейзаже: [сборник] / Мария Метлицкая - Метлицкая Мария (Женские судьбы, 2021)
Экземпляры: (20210714) / Инвентарный номер: 41699 / Цена: 617.43 / Сис.шифр: 84(2Рос=411.2)6 / Авт.знак: М 54 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=411.2)6